Enterprise Architecture Planning at KSP Artha Nugraha Klaten Using Enterprise Architercture Planning (EAP) - Elisabeth Christina Sari; Bambang Soedijono; Asro Nasiri (Jurnal Mantik, 2022)
In the era of technological development in today's era, almost all fields use technology to support performance so that it gets faster and increases. This also applies to cooperatives. The Artha Nugraha Savings and Loan Cooperative is a private cooperative that is developing in Klaten Regency. This cooperative, located in Klaten Regency, requires the use of information technology in developing technology for better operational governance, of course, by maintaining the goals of the cooperative. The main activities of the cooperative are registering new members, savings and loan business functions, managing savings and loan reports and member resignations, supported by supporting activities, namely administrative management and HR management. Therefore, to speed up work in cooperatives, careful planning is needed, using the Enterprise Architecture Planning (EAP) method to help strategically design a process in the development of information technology in the form of enterprise architecture. The results of the design that has been made will produce a data architecture, an application architecture, and a technology architecture that will make it easier for officers or cooperative management to obtain accurate, relevant, and fast information.